Pertumbuhan teripang Gamat Lumpur (Stichopus hermanii) pada lokasi budidaya dengan substrat berbeda di Teluk Talengen Kabupaten Kepulauan Sangihe - Tarimakase, Yulianus; Ngangi, Edwin L.A.; Kusen, Diane J.; Sambali, Hariyani; Tumembouw, Sipriana S.; Wantasen, Adnan S.; Salindeho, Indra R. (e-Journal BUDIDAYA PERAIRAN, 2020)
This study aimed to analyze the growth of sea cucumber gamat (Stichopus hermanii) on different substrates. This research was conducted in the waters of Talengen Bay, Tabukan Tengah District, Sangihe Islands Regency. The implementation time starts from January - February 2020 for 42 days of research. This research consisted of 3 treatments: A (mud substrate), B (sandy mud substrate), and C (sandy substrate and coral splinter), each treatment consisted of 3 replications. In each experimental unit, four sea cucumbers were placed. This research used a net made from tagaho, with an iron frame which is divided into 3 parts. The size of the container was 30 x 30 x 30 cm3. The results showed that the best absolute length of sea cucumber gamat was the in Treatment A (6.17 cm), then Treatment B (4.67 cm), and Treatment C (1.25 cm). The results of the analysis of the daily growth rate: Â Treatment A (1.17%) got the best growth rate results compared to Treatment B (0.87%) and Treatment C (0.29%).